2009
DOI: 10.1038/ki.2009.387
|View full text |Cite
|
Sign up to set email alerts
|

COMP-Angiopoietin-1 decreases lipopolysaccharide-induced acute kidney injury

Abstract: During sepsis endothelial dysfunction is an important pathogenetic mechanism in acute kidney injury (AKI). Lipopolysaccharide (LPS)-induced endotoxemia is associated with renal hemodynamic changes such as alterations of renal blood flow (RBF), vascular resistance, and glomerular filtration rate. We used adenoviral delivery of an engineered variant of native angiopoietin-1 (COMP-angiopoietin-1) containing anti-inflammatory and anti-permeability functions, to determine if regulation of renal endothelial cell dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…The reason why no influence of the CYP down-regulation was noted in toxicokinetics of DCF remains unclear although the time lag up to the onset of CYP down-regulation may have contributed. Moreover, regarding the delayed elimination of 5-OH-DCF from plasma, the decreased clearance by LPS-induced alterations in blood flow (Kim et al, 2009), transporters or phase II enzymes (Yano et al, 2010) may explain the differences observed between the results of in vitro and in vivo experiments. For example, LPS is known to downregulate the multidrug resistance-associated protein 2 (Mrp2) that mediates canalicular secretion of several amphiphilic organic anions including glucuronides and GSH conjugates (Yano et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…The reason why no influence of the CYP down-regulation was noted in toxicokinetics of DCF remains unclear although the time lag up to the onset of CYP down-regulation may have contributed. Moreover, regarding the delayed elimination of 5-OH-DCF from plasma, the decreased clearance by LPS-induced alterations in blood flow (Kim et al, 2009), transporters or phase II enzymes (Yano et al, 2010) may explain the differences observed between the results of in vitro and in vivo experiments. For example, LPS is known to downregulate the multidrug resistance-associated protein 2 (Mrp2) that mediates canalicular secretion of several amphiphilic organic anions including glucuronides and GSH conjugates (Yano et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Ang-1 attenuates thrombin-induced permeability in human pulmonary microvascular endothelial cells (HPMVECs) by enforcing the VE-cadherin organization [10]. Ang-1 could counteract the inflammatory effects of vascular endothelial growth factor (VEGF) on endothelial cells [11], ameliorate ROS-induced acute lung injury [12] and lipopolysaccharide-induced acute kidney injury [13] by reducing the induction of ICAM-1 and VCAM-1, causing a reduction in leukocyte adhesion and subsequent inflammation. While Ang-1 has been shown to have a protective effect against inflammation, Ang-2 has been shown to have the opposite effect.…”
Section: Pathophysiologic Mechanisms Of Myocardial I/r Injury and Thementioning
confidence: 99%
“…During endotoxemia, the vascular endothelial cells are affected by the inflammatory cytokines that induce the expression of cell adhesion molecules, such as ICAM-1, VCAM-1, and fractalkine (9,16). Following the expression of cell adhesion molecules, inflammatory cells, such as neutrophil and polymorphonuclear cells migrate into the tissue and are activated at the site of inflammation (18).…”
Section: Discussionmentioning
confidence: 99%
“…As endotoxemia is associated with increased myocardial vascular permeability, we examined the effect of JANEX-1 on the endotoxemia-induced vascular leakage of Evans blue dye (16). Endotoxemia significantly increased the vascular leakage, and this effect was significantly reduced by pretreatment with JANEX-1 (Fig.…”
Section: Janex-1 Improves Myocardial Vascular Leakage By Decreasing Smentioning
confidence: 99%
See 1 more Smart Citation